Role of an Exosomes-Related lncRNAs Signature in Tumor Immune Microenvironment of Gastric Cancer - Li, Chan; Zhang, Zeyu; Peng, Emin; Peng, Jinwu (Frontiers in Cell and Developmental Biology, 2022)
Background: Exosomes plays a crucial role in intercellular communication of gastric cancer (GC), while long non-coding RNAs (lncRNAs) contributes to the tumorigenesis and progression of GC. This study aims to explore the prognostic exosomes-related lncRNAs of GC patients. Methods: Data of 375 GC patients were obtained from the TCGA database. The entire cohort was randomly divided into a training cohort and a validation cohort in a 2:1 ratio. Exosomes-related lncRNAs were identified by the Pearson correlation analysis with reported exosomes-related genes. LASSO Cox regression was used to construct the signature. Results: A prognostic signature consisting of 11 exosomes-related lncRNAs was identified, and patients with lower risk scores had a better prognosis than those with higher risk scores. ROC curves and multivariate Cox regression analysis showed that the signature was an independent risk factor for prognosis in both the training (HR: 3.254, 95% CI: 2.310–4.583) and validation cohorts (HR: 1.974, 95% CI: 1.108–3.517). Gene set enrichment analysis (GSEA) suggested associations between the signature and several immune-related pathways. The identified signature was shown to be associated with GC tumor microenvironment. The expression of two immune checkpoints was also increased in the high-risk group, including B7-H3 and VSIR, indicating the potential role of the identified signature in GC immunotherapies. Conclusion: A novel exosomes-related lncRNA signature, which may be associated with tumor immune microenvironment and potentially serve as an indicator for immunotherapy, has been identified to precisely predict the prognosis of GC patients.